2000
DOI: 10.1046/j.1524-4725.2000.99287.x
|View full text |Cite
|
Sign up to set email alerts
|

Ber-EP4-Positive Phenotype Differentiates Actinic Keratosis from Superficial Basal Cell Carcinoma

Abstract: Ber-EP4 staining reliably distinguishes AK from superficial BCC. The lack of Ber-EP4 staining of AK supports the currently accepted pathogenetic dogma that SIN and SCC arise from AK, but BCC does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Actinic keratoses included in our study failed to stain for EpCAM with both antibodies studied, which is consistent with previous reports 16,17…”
Section: Discussionsupporting
confidence: 93%
“…Actinic keratoses included in our study failed to stain for EpCAM with both antibodies studied, which is consistent with previous reports 16,17…”
Section: Discussionsupporting
confidence: 93%
“…Basal cell carcinoma is the most common cutaneous carcinoma, accounting for nearly 70% of all skin malignancies (7)(8)(9)(10)(11)(12). Although a subset of that tumor type can exhibit aggressive behavior (8), most basal cell carcinomas are cured by conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the theory that BCCs arise from epithelial germ cells including some identified in vellous hairs could be supported 25 . SCCs have been negative for Ber‐EP4, and therefore, it has been suggested that this antibody could be utilized in the distinction of basal cell from SCC and actinic keratosis in occasions where there is such difficulty 26,36 . Additionally, this antibody has been used successfully in Mohs micrographic surgery when BCC nests are masked by inflammation 37 …”
Section: Discussionmentioning
confidence: 99%